Alteration of Membrane Cholesterol Content Plays a Key Role in Regulation of Cystic Fibrosis Transmembrane Conductance Regulator Channel Activity - Cui, Guiying; Cottrill, Kirsten A.; Strickland, Kerry M.; Mashburn, Sarah A.; Koval, Michael; McCarty, Nael A. (Frontiers in Physiology, 2021)
Altered cholesterol homeostasis in cystic fibrosis patients has been reported, although controversy remains. As a major membrane lipid component, cholesterol modulates the function of multiple ion channels by complicated mechanisms. However, whether cholesterol directly modulates cystic fibrosis transmembrane conductance regulator (CFTR) channel function remains unknown. To answer this question, we determined the effects of changing plasma membrane cholesterol levels on CFTR channel function utilizing polarized fischer rat thyroid (FRT) cells and primary human bronchial epithelial (HBE) cells. Treatment with methyl-β-cyclodextrin (MβCD) significantly reduced total cholesterol content in FRT cells, which significantly decreased forskolin (FSK)-mediated activation of both wildtype (WT-) and P67L-CFTR. This effect was also seen in HBE cells expressing WT-CFTR. Cholesterol modification by cholesterol oxidase and cholesterol esterase also distinctly affected activation of CFTR by FSK. In addition, alteration of cholesterol increased the potency of VX-770, a clinically used potentiator of CFTR, when both WT- and P67L-CFTR channels were activated at low FSK concentrations; this likely reflects the apparent shift in the sensitivity of WT-CFTR to FSK after alteration of membrane cholesterol. These results demonstrate that changes in the plasma membrane cholesterol level significantly modulate CFTR channel function and consequently may affect sensitivity to clinical therapeutics in CF patients.